HIV related stigma, perceived social support and risk of premature atherosclerosis in South Asians - Bergmann, Travis (Indian Heart J, 2018)
OBJECTIVE: This study sought to determine the association between social support and stigma experienced by HIV-positive patients and presence of subclinical cardiovascular disease. METHODS: We implemented a cross sectional study in 67 HIV-positive patients and 52 controls from a community health care center in central India. The participants underwent an in-depth survey and a clinical and laboratory assessment of cardiovascular risk. Carotid-intimal thickness (CIMT) was used as a marker of subclinical cardiovascular disease. RESULTS: On comparing the HIV and age and sex-matched control population, HIV patients had lower body weight (P=<0.001), and lower systolic blood pressures (P = 0.002). Despite the lack of higher cardiac risk factor prevalence and lower lipid abnormalities, HIV patients had higher right, left and average CIMT values than controls (P < 0.001 for all). HIV patients also showed higher prevalence of abnormal CIMT (≥ 0.9 mm) than controls (32% vs. 0%, P < 0.001). HIV patients with increased CIMT (n = 37) in comparison with those with normal CIMT (n = 30) were more frequently males (P = 0.023), had higher systolic blood pressures (P = 0.002), lower CD4 counts (P = 0.033) and experienced higher enacted stigma (P = 0.044). On multivariable stepwise logistic regression, systolic blood pressure (odds ratio:1.06, P = 0.002) and stigma score > 25(th) percentile value (odds ratio:3.84, P = 0.037) were independent predictors of the abnormal CIMT. CONCLUSIONS: HIV-positive patients from central India have a higher prevalence of abnormal CIMT as a marker of subclinical cardiovascular disease than the general population. This predisposition to increased cardiovascular risk may be related to complex interactions between HIV disease and stigma-related healthcare inequalities.